Effectiveness of Constructivism Instructional Method on Students’ Psychomotor Achievement, Problem-Solving and Retention in Mechanical Engineering Craft Practice in Technical Colleges - Eze, Titus. I.; Onwusa, Sylvester Chukwutem; Olumoko, Bamidele Oluyinka; Sanni, Rotimi Akinwale (Advances in Social Sciences Research Journal, 2020)
The poor academic achievement of students in technical colleges in Nigeria has been a major concern to researchers. It is believed that the application of effective instructional methods in technical colleges could enhance overall students’ academic achievement. This demands that teachers in technical colleges should adopt instructional methods that could enhance overall achievement particularly in students’ psychomotor, problem solving achievement and enhance retention in mechanical engineering craft practice in technical colleges. The study investigated the effectiveness of constructivism instructional method on students’ psychomotor achievement, problem-solving and retention in mechanical engineering craft practice in technical colleges in Delta State. Three research questions guided the study and three null hypotheses were tested at 0.05 level of significance. The study adopted the quasi-experimental research design. Population of the study was 97 vocational II mechanical engineering craft practice (MECP) students in the six technical colleges in Delta State. A sample of 82 was used for the study. Instruments for data collection were Mechanical Engineering Craft Practice Achievement Test (MECPAT) and the lesson plans for the experimental and control groups. The instruments- MECPAT and lesson plans; were face and content validated by three experts, two from the Department of Technology and Vocational Education and one from Measurement and Evaluation Unit of the Department of Educational Foundation; all in Nnamdi Azikiwe University Awka. Test–retest method was used to establish reliability of MECPAT and was calculated using Pearson Product Moment Correlation which yielded a correlation coefficient value of 0.87. Arithmetic mean was used to analyze data relating to research questions and while analysis of covariance (ANCOVA) was used to test the null hypotheses. Findings revealed that students taught mechanical engineering craft practice using constructivism instructional method performed better, possessed requisite problem solving skills and had better knowledge retention than those taught with lecture teaching method (LTD). Based on the findings, it was concluded that constructivism instructional teaching method (CITM) is an effective and efficient mode of instruction with capacity of improving students’ learning outcome, problem solving techniques and retention ability level. Consequently, it was recommended among others that technical teachers should use constructivism instructional method in teaching mechanical engineering craft practice so as to enhance students’ psychomotor achievement in subsequent public examination.